Karakteristik Karkas Bandikut (Echymipera kalubu) di Kampung Wafmana, Distrik Mawabuan, Kabupaten Tambrauw: Carcass Characteristics Of Bandikut (Echymipera kalubu) In Wafmana Village, Mawabuan Distrik, Tambrauw Regency - Piter Asiar; Frandz Rumbiak Pawere; Johan F Koibur (Fakultas Peternakan Universitas Papua, 2019)
The research purpose to identify and investigate the carcass characteristics of bandicoot (Echymipera kalubu) in Wafmana Village Distric of Mawabuan Tambrauw Regency West Papua Province. The material used in this study were 20 head bandicoot ages ± 4 month were classified in to 2 groups consist of 10 head males bandicoot and 10 head females bandicoot. The research method was exploration. The results showed that body weight of males and females bandicoot were 1245,4 ± 484,38 g and 710,95 ± 252,27 g (P<0,05). Carcass weight of males and females bandicoot were 1245,4 ± 484,38 g and 710,95 ± 252,27 g (P<0,05). Carcass percentage of males and females bandicoot were 76,28 ± 6 % dan betina 75 ± 5 % (P>0,05). Weight cut fore quarter of males and females bandicoot were 580,86±245,72 g and 300,17±105,93 g (P<0,05). Weight cut hind quarter of males and females bandicoot were 629,52±233,55 g dan 350,63±123,79 g (P<0,05). Fore Carcass percentage of males and females bandicoot were 45,98±2 % and 42,63±4 % (P<0,05). Hind carcass percentage of males and females bandicoot were 50,98±4 % and 49,53±4% (P>0,05). Keywords: carcass characteristcs, Echymipera kalubu